Immunotherapy partners after progression: Right place, right time? - Rouhani, Sherin J.; Bestvina, Christine M. (Cancer, 2023)
This editorial aims to place the trial of pembrolizumab plus next line chemotherapy by Salous et al. in the context of other clinical trials evaluating different strategies to extend the benefit of immunotherapy after disease progression. Included in this article are the INSIGNA trial, off‐protocol treatment beyond progression, local ablative therapy with radiation, the recently published Lung‐MAP S1800A study, and a summary of other immunotherapy‐based combinations currently under investigation.